Sexual selection on jumping spider color pattern: investigation with a new quantitative approach. (14th April 2021) - Zhou, Wei; Yu, Long; Kwek, Bernetta Z W; Jin, Ge; Zeng, Hua; Li, Daiqin
Abstract: How animals assess information encoded in individual color patches have been extensively studied, yet the role of both individual color patches and gross color pattern (i.e., the combination of color patches) remains understudied. We tested the functioning of both individual color patches and gross color pattern in sexual selection using the jumping spider Siler semiglaucus as a study system. We first quantified sexual dimorphism in S. semiglaucus in both individual patches and gross color pattern using the newly developed quantitative color pattern analysis (QCPA) framework. After detecting sexual differences in color coverage and pattern contrast, we manipulated the abdomen color pattern of males and had them engage in both female mate choice and male contest trials. Females spent more time watching males with lower pattern contrast and greater red coverage during mate assessment, suggesting that they evaluate information from both individual patches and gross color pattern of males. However, male color pattern had no significant effect on the outcomes of male contests. Thus, we suggest that the observed sexual color pattern dimorphism evolved primarily through female mate choice in S. semiglaucus . This is the first study to use QCPA framework to quantify sexual dimorphism in within-pattern conspicuousness from an intraspecific perspective in invertebrates. Our study also highlights the importance of both individual color patches and gross color pattern in sexual selection. Abstract : Males and females are strikingly different in color patterns, which is likely sexually selected. However, it is difficult to quantify such a difference. By applying a newly developed quantitative color pattern analysis framework, we quantify sexual dimorphism in color patterns in a jumping spider. We find that male abdomen color pattern is shaped exclusively by female mate choice. Our study sheds new light on the importance of global color patterns in sexual selection.